نظام تكاليف الأنشطة كأساس لقياس تكلفة الخدمات التعليمية بالجامعات - حلس، سالم عبدالله سالم (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2007)
يهدف هذا البحث بصورة رئيسية لاستخدام مدخل المحاسبة عن التكلفة على أِساس النشاط (ABC) في مجال قياس وترشيد تكلفة الخدمات التعليمية، وتوفير المعلومات اللازمة في مجال ترشيد القرارات الإدارية، وتحديد أسعار تلك الخدمات في الجامعات على أسس موضوعية دقيقة. وفي إطار محاولة تحقيق أهداف البحث تم استخدام المنهج الاستقرائي وذلك لمراجعة أدبيات الدراسة وتم استخدام المنهج الاستنباطي لدراسة مدى إمكانية استخدام نظام تكاليف الأنشطة لتوفير البيانات اللازمة لمعالجة القصور واستنباط أوجه التطوير الممكنة لقياس وترشيد تكلفة الخدمات التعليمية. ولقد خلصت الدراسة إلى النتائج التالية : 1- إمكانية التغلب على المشكلات المرتبطة باستخدام الطرق التقليدية لتخصيص وتوزيع التكاليف غير المباشرة، وذلك باستخدام نظام تكاليف الأنشطة في استخراج معدلات تكلفة لكل نشاط على حسب محركات التكلفة المناسبة لكل منها. 2- إمكانية التغلب على مشكلة التحميل الرأسمالي. 3- أن التسعير على أساس بيانات التكاليف يفيد كلا من إدارة الجامعة والمتعاملين معها وبما يسهم في زيادة الوعي التكاليفي، والذي ينعكس أثره على الاستخدام والتشغيل الاقتصادي للموارد المتاحة والمستخدمة بما يحقق الأهداف المرغوبة منها. 4- إمكانية استخدام أسلوب التكلفة المستهدفة في مجال تسعير الخدمات التعليمية . The main objective of this research is the effective use of the accounting approach to calculating costs. This approach is based on Activity Based Costing (ABC) which is used in assessing and controlling the cost of educational services; in addition, it provides the necessary data which is used in accurate identification of administrative decision as well as the cost of services provided by universities. In the process of achieving the main objective of the study, the deductive approach has been used while surveying literature review. The same approach has been used to examine the possibility of using ABC in providing the data required to tackle points of weakness, and in effect, developing and orienting the cost of educational services. Accordingly , the research has reached the following conclusions: 1-It has been found out that the new system can help in overcoming the problems related to the use of the traditional system in; the ABC helps in assessing the indirect cost and determining the average cost of each activity in accordance with the suitable cost stimulators. 2-The ABC can overcome the problems emerging from charging on capitals. 3-Pricing based on ABC is useful in the administration of universities in the sense of raising awareness of cost. This will be reflected on employing the available resources to achieve the desired goals. 4-It is possible to use the target cost in pricing educational services.
791257 676547 626484 693001 626495
Keywords: تكلفة الخدمات التعليمية -- الجامعات الفلسطينية -- المصاريف الجامعية